UMP, PERODUA establish strategic partnership to offer BTech Apprenticeship programme - Mimi Rabita, Abdul Wahit (2021)
KUALA LUMPUR, 12 April 2021 - The collaboration between Universiti Malaysia Pahang (UMP) and PERODUA Group will strengthen the country’s Technical and Vocational Education and Training (TVET) programme through the offering of the Bachelor of Technology (BTech Apprenticeship) programme which uses the German Engineering education model (Fachhochschule) in the education system in the country.